Tulong hindi kulong attaining juvenile resilience through rehabilitative environment - Llorente, Kathleen Alexis C. (College of Architecture, University of the Philippines Diliman, 2023)
Despite the decline in juvenile delinquency from the previous years, records demonstrates a surge within younger age groups of minor violators. This subject is of great concern as it has incited discussions on lowering the minimum age of crime responsibility from 15 years to 9 years old despite the lack of community-based early intervention and diversion programs and the inadequate enforcement of existing rehabilitation programs for juvenile delinquents. As children and youth are recognized as primary agents of change and advancement, addressing juvenile delinquency should be given priority. This study explores rehabilitative architectural interventions with Care Farming practice in designing a comprehensive youth resilience center to implement a community-based holistic early intervention program for younger marginalized groups with higher vulnerability to committing offenses and exposure to violent environments. The scant resources for agri-related rehabilitation facilities in the context of the new normal limit options in the efficient design of rehabilitative spaces for juvenile offenders. Applying a positive youth development approach in rehabilitative space will aid in designing a prosocial and nurturing environment for children at risk and young offenders in contrast with the punitive and isolative design of institutional spaces. Examining the positive spatial qualities of rehabilitation centers and integration of therapeutic features of Care Farming provides a potential course of action in attaining children and youth resilience against delinquency.